2012
DOI: 10.1158/0008-5472.sabcs12-p4-13-01
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P4-13-01: Racial Disparities in the Incidence of Dose-limiting Chemotherapy Induced Peripheral Neuropathy

Abstract: Objective: To determine the incidence of and risk factors for dose-limiting chemotherapy induced peripheral neuropathy (CIPN) in non-metastatic breast cancer. Methods: This retrospective cohort study included 488 women with an adjuvant or neoadjuvant treatment plan with docetaxel or paclitaxel from June 1, 2009 to December 31, 2011. Exclusion criteria were: metastatic disease, previous neurotoxic chemotherapy, pre-existing neuropathy, pregnant or within 3 months post-partum, and prosthetic limb.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Peripheral Neuropathy and Cardiotoxicity. Two studies observed statistically significantly higher incidence of peripheral neuropathy among black cancer patients as compared with non-Hispanic white breast cancer patients treated with taxanes (98,137). By comparison, one other study did not (97).…”
Section: Quality Of Lifementioning
confidence: 98%
See 1 more Smart Citation
“…Peripheral Neuropathy and Cardiotoxicity. Two studies observed statistically significantly higher incidence of peripheral neuropathy among black cancer patients as compared with non-Hispanic white breast cancer patients treated with taxanes (98,137). By comparison, one other study did not (97).…”
Section: Quality Of Lifementioning
confidence: 98%
“…Very little information is available regarding the potential relationship between obesity and peripheral neuropathy. In breast cancer, two studies observed no association between obesity and chemotherapy-induced peripheral neuropathy after taxane administration (97,98). Further, a study among multiple myeloma patients found that obesity did not increase the risk of peripheral neuropathy (99).…”
Section: Peripheral Neuropathymentioning
confidence: 99%